Healing the heart a spiritual approach to reversing coronary artery disease - Chopra, Deepak (Rider, 1998)
Drawing on the ancient Ayurvedic system of medicine and Western scientific research, this book examines how the link between the body and mind can play a major part in preventing heart disease.